Ocean acidification - Gattuso, Jean-Pierre; Hansson, Lina (Oxford University Press, 2011)
The ocean helps moderate climate change thanks to its considerable capacity to store CO₂, through the combined actions of ocean physics, chemistry, and biology. This storage capacity limits the amount of human-released CO₂ remaining in the atmosphere. As CO₂ reacts with seawater, it generates dramatic changes in carbonate chemistry, including decreases in pH and carbonate ions and an increase in bicarbonate ions. The consequences of this overall process, known as "ocean acidification", are raising concerns for the biological, ecological, and biogeochemical health of the world's oceans, as well as for the potential societal implications. This research level text is the first to synthesize the very latest understanding of the consequences of ocean acidification, with the intention of informing both future research agendas and marine management policy